Biogasoline production from waste cooking oil using nano-cobalt molybdenum catalyst - Mabika, Kudzai (My University, 2016)
The world is gradually shifting to renewable clean energy and away from fossil fuels which are considered to have a finite reserve and have negative impact on the environment. Many alternatives have been developed including biofuels. Of the biofuel family, not all products are produced at the same level given the differences in technological advancements. Commonly produced biofuels which are commercialised are bioethanol and biodiesel. Given that a large number of vehicles operate using gasoline, there is a need to develop biogasoline specific processes to produce biogasoline. Bioethanol is used as a blending agent and has a drawback of engine corrosion. Biogasoline can be used for blending or to substitute gasoline in existing motors. The main objective of the project was to produce biogasoline from waste cooking oil using nano-particle catalyst for better performance. A Co-Mo/Al2O3 catalyst was synthesized and tested in two processes namely thermal cracking and hydrocracking. The waste cooking oil used in this study was pre-treated to remove salts and excess water prior to cracking process. Various analytical techniques were then used to characterize the catalyst, waste cooking oil and the products. Waste cooking oil was successfully pre-treated for salt removal with salt dropping from 13.18% to 4.37%. Effect of catalyst performance on thermal cracking proved to be minimal with temperature being the major factor in cracking. The catalyst performed better under hydrocracking with effects of catalyst calcination temperature and catalyst/oil ratio being more apparent as opposed to thermal cracking. Highest percentage biogasoline achieved under thermal cracking was 81.6% at a reaction temperature of 600°C. The highest percentage biogasoline achieved under hydrocracking was 75.7% at a reaction temperature of 210°C, using calcined catalyst at 700°C, catalyst/oil mass ratio of 1/75 and reaction time of 1hr. The biogasoline produced had low sulphur content. The highest sulphur containing product for hydrocracking was 7.4% and that for thermal cracking was 1.3%. It is recommended that the hydrocracking and thermal cracking methods be used for biogasoline production and that further research be done on the optimization of the biogasoline production process and synthesis of nano Co-Mo catalyst.
Thesis (M.Sc. (Eng.))--University of the Witwatersrand, Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, 2016.
Keywords: Ethanol as fuel; Biomass energy; Renewable energy sources; Catalysts; Oils and fats--Biotechnology; Hydrocracking